Maternal stress and adolescent brain structure and function - Niehaus, Claire E. (Brain Behav, 2019)
INTRODUCTION: Adolescence is a time of heightened sensitivity in biological stress systems and the emergence of stress‐related psychopathology. Thus, understanding environmental factors in adolescence that might be associated with adolescents'’ stress systems is important. Maternal stress levels may be involved. However, the relationship between maternal stress and the adolescent brain is unknown. METHOD: The present study examined the association between mothers' self‐reported stress levels and mothers' cortisol stress reactivity and their early adolescents' brain structure and functional activation to stressful negative emotional images. Participants included 66 mothers and their 12‐ to 14‐year old adolescents. Mother's perceived stress and salivary cortisol reactivity to a stressful task were collected. Then, adolescents' brain structure and function were assessed in a magnetic resonance imaging session. RESULTS: Functional whole‐brain analyses revealed that mothers' higher reported perceived stress, but not cortisol reactivity, predicted adolescents' higher responses in the medial prefrontal cortex (mPFC) to stressful negative emotional stimuli. There were no statistically significant associations for structural analyses. CONCLUSIONS: Given the finding of maternal stress reactivity related to adolescent mPFC function—an integral structure related to stress responses—parent stress may play a role in the development of neural stress systems in adolescence, with potential implications for development of psychopathology.